Investigation of the kinetic parameters of the process of extraction of nickel (ІІ) hydroxide buffer ammonia and chloride amon - Юрченко, Ганна Олександрівна; Бутенко, Анатолій Миколайович (Eastern-European Journal of Enterprise Technologies, 2012)
The article describe a hydrometallurgical method of nickel (II) selective extraction from secondary raw material using ammonia solution. The main aim of the research is to define kinetic parameters of the process. An optimal composition of a buffer solution for nickel (II) selective extraction and molar ratio of its ingredients, that were defined by authors, gave important data base for studying kinetics of the buffer solution interaction with initial secondary raw material that contains nickel. Modern analysis techniques usage allows to accomplish control of completeness of nickel extraction. Mathematical treatment allows to get important dependences of nickel (II) rate of extraction on temperature and contact time, that are required for calculation of kinetic parameters of the process. A technique to calculate the kinetic parameters allows to get essential information that is important in choosing a better hydrometallurgical method of treatment of secondary raw material that contains nickel. The main goal it is implementation in industry. The obtained results can be used in inorganic synthesis and non-ferrous metal production from a secondary raw material. Defined kinetic parameters of the process allow to optimize it both technologically and economically.